Physicochemical property of starch–pectin conjugates with resistance to enzymatic activity. (1st November 2013) - Zhang, Juan; Chen, Lei; Cui, Junhui; Xiao, Lin; Wang, Zhengwu
Abstract BACKGROUND In view of the high nutritional values and bioactivities of resistant starch and pectin, it would be a good choice to chemically combine pectin and starch to give a new type of chemically modified resistant starch. RESULT A new type of chemically modified resistant starch has been prepared by cross‐linking starch and pectin using sodium trimetaphosphate. Starch–pectin conjugates can well prevent the hydrolysis catalysed by different enzymes, such as α‐amylase, amyloglucosidase, pancreatin as well as β‐amylase and glucosidase. Although the conjugates do not change the crystal type of starch, they increase the degree of crystallinity. Moreover, thermal stability and structural homogeneity of the conjugates are positively correlated with double‐helical order in the crystalline region. CONCLUSION This study gives a new method for the preparation of resistant starch–pectin conjugates which can be widely used as a new type of food additive in the industry. © 2013 Society of Chemical Industry